Islamofobia dalam Filem Barat: Analisis Kritis dalam filem American Sniper dan 13 Hours: The Secret Soldiers of Benghazi: Islamophobia in Western Films: An Analysis Critics on American Sniper and 13 Hours: The Secret Soldiers of Benghazi - Wan Mohamad, Wan Rashidah Hanim; Siren, Nor Raudah (Jurnal Usuluddin, 2020)
Recently, the phobic nature of Islam has gripped Western society called ‘Islamophobia’. Islamophobia has existed for so long but has risen over the last decade, after the September 11, 2001, terrorist attack that destroyed the World Trade Center building in New York, USA. Muslim are targeted for their religious ethical and moral beliefs, with the growing tensions of Islamophobia around the world, especially in the West. Additionally, hatred and phobia towards Islam are often expressed through filming. Most of the emergence of this anti-Islamic propaganda film is from the West because the Islamophobic wave itself sparks from the West. Films produced often illustrate the dark side of Islam and Muslim themselves. The film titled American Snipers and 13 Hours: The Secret Soldiers of Benghazi were known to sow the seeds of Islamophobia through the dark side exposure to Islam and adherents such as displaying Arabs as terrorists. These anti-Islamic propaganda films are a problem for the germination of Islamophobia among non-Muslims. Islamophobia is one of the anti-Islam messages. Therefore, this article will identify the Islamophobic messages applied in American Sniper and 13 Hours: The Secret Soldiers of Benghazi. This study also led to a discussion of the Islamic perspective on Islamophobia. The results of the data analysis found that the film studied was a propaganda film that featured anti-Islam propaganda through Islamophobia in the aspect of cinematography and film screenplay whether it was presented clearly or hidden.